Renewable energy investments for sustainable business projects - Dinçer, Hasan; Yüksel, Serhat (Emerald Publishing Limited, 2023)
With such a wide range of social and economic uses, energy has become essential to global infrastructure and operations, regardless of economic or environmental cost. Renewable energy sources, where energy is obtained from natural sources such as the sun and wind, currently stand as important alternatives to fossil fuels. Yet their comparatively high installation costs continue to deter investors and further propel the planet towards catastrophic climate change. Conscious of these complexities, Renewable Energy Investments for Sustainable Business Projects identifies multiple solutions for improving the appeal of renewable energy projects. Breaking down myths about their viability and practicality, Hasan Dinçer and Serhat Yüksel take a variety of issues into consideration, including finance, competition, risk management, customer relations, technological factors and learning and growth to formulate a practical rather than theoretical examination of renewable energies and their potential. From tax advantages to hydrogen sourcing, Renewable Energy Investments for Sustainable Business Projects explores a variety of the latest practices and technological developments surrounding renewable energy, offering practical insight and tangible advice to academics and researchers in environmental management.